Rádio USP, a FM que toca todas as línguas - Trigo, Lígia (Comunicação & Educação, 1996)
Radio USP celebrated its 18 year anniversary and keeps today an ecletic programming, mixing news, information, music and educational projects. It has been searching an approach between the University and society, showing its production and, at the same time, becoming different form the others in Sao Paulo.